Chemical and Biological Pretreatments on Sugarcane Bagasse to Enhance its Enzymatic Hydrolysis. Issue 15 (23rd May 2017) - Hernández, Christian A.; Ziarelli, Fabio; Gaime, Isabelle; Farnet Da Silva, Anne Marie; García, Gabriela; García‐Pérez, José A.; Gutiérrez‐Rivera, Beatriz; Alarcón, Enrique
Abstract: Alkaline and biological lignocellulose pre‐treatments are commonly used to enhance enzymatic hydrolysis and improve ethanol production. In this study, 13 C CPMAS NMR spectroscopy was used to describe changes in sugarcane bagasse (SCB) pre‐treated with NaOH, Ca(OH)2 and with Pycnoporus sanguineus . Changes in the contents of alkyl C, Carboxyl C, Aromatic C (tertiary, quaternary and p‐hydroxyphenyl C), O ‐alkyl C, amino acids, ergosterol and chitin, as well as in the crystallinity index of cellulose were observed. Through a multivariate analysis, relations between changes in the chemical composition of SCB and enzymatic hydrolysis were established. P. sanguineus promotes better lignin decay, glucose release and hydrolysis yields than chemical pre‐treatments, and increases the amount of amino acids and ergosterol in SCB, while NaOH increases the cellulose crystallinity index. The hydrolysates were fermented with Saccharomyces cerevisiae for 96 h, and analysed through HPLC. The initial composition of the hydrolysates [mg.ml −1 ] and biomass production (cells.ml −1 ) were then related to the ethanol production and fermentation yields. We found that ethanol production and fermentation yields were negatively correlated with cell growth in Saccharomyces, but positively correlated with glucose consumption in the P. sanguineus pre‐treatment. We conclude that the biological pre‐treatment using P. sanguineus in the conditions hereby described, has a potential to increase ethanol productivity. Abstract : One of the main obstacles to enhance ethanol production from lignocellulose is the barrier posed by lignin to the release cellulose and to gain in sugars to be fermented. The effect of a chemical and biological treatments of lignocellulose on the sugars released and on ethanol production is shown. The intensity of aromatic C (lignin) signals, measured with 13 C CPMAS NMR, decreased in pre‐treatments with both NaOH and Pycnoporus sanguineus ).